Biochemical Profile and Productive Performance in Dairy Cows with Lameness During Postpartum Period - Paiano, Renan Braga; Birgel, Daniela Becker; Ollhoff, Rüdiger Daniel; Birgel Junior, Eduardo Harry (Acta Scientiae Veterinariae, 2019)
Background: Lameness in dairy cows is classified as a gait change caused by multifactorial process. The phase of the peripartum causes intense physiological changes for the adaptation of late gestation and onset of lactation. The aim of this study was to characterize the changes in the biochemical profile and productive performance in dairy cows with lameness during postpartum period. Materials, Methods & Results: This study was conducted at the University of São Paulo farm, in Pirassununga, São Paulo State, Brazil, from January to March 2017. A total, of 48 multiparous (2 to 3 lactations and 3-4 years old) dairy cows, that had the milk production of 9,200 kg/ dairy cow in a period of 305 days in the previous lactation, were included in the study. All cows were managed under the same conditions and nutritional regimen. Evaluation of body condition score was performed by a single person on -18, -12, -8, -5, and -2 days before parturition, at parturition, and on days 1, 7, 14, 21, 30, 45 and 60 after parturition. Milk production was recorded on days 7, 14, 21, 30, 45 and 60 after parturition and saved in the software program. Blood samples were performed on -18, -12, -8, -5, and -2 days before parturition, at parturition, and on days 1, 7, 14, 21, 30, 45 and 60 after parturition. Blood samples were assayed for albumin, calcium, cholesterol, triglycerides, non-esterified fatty acids, β-hydroxybutyrate, urea, creatinine, gamma-glutamil-transferase and total protein concentrations. Dairy cows were divided into a lame group (11) and normal group (37) based on locomotion score from parturition to seven days postpartum. Lame cows was classified if their score was > 2, and normal cows was classified if their score was ≤ 2 and free of any disease. Dairy cows that suffer by any health disorder other than lameness were excluded from this study. Cow diagnosed with lameness outside the diagnostic period were excluded from this study. The averages of the milk production, body condition score and biochemical profile were compared with the Tukey’s test. Lame cows showed lower (P < 0.05) concentrations of albumin (on days -18 -12, -8, -5, -2 relative to parturition, at parturition, and on days 7, 14, 21, 45 and 60 after parturition) calcium (on days -18, -12, -8, -5 and -2 before parturition, and on days 7, 14, 21, 45 and 60 after parturition), cholesterol (on days -12, -8, -5 before parturition and on days 7, 14, 21, 30, 45 and 60 after parturition) than normal cows. Cow with lameness showed higher (P < 0.05) concentration of triglyceride (on days 7, 14, 21, 30, 45 and 60 after parturition), non-esterified fatty acids (on days 1, 7, 14, 21, 30, 45 and 60 after parturition) and β-hydroxybutyrate (on days -12, -5 and -2 before parturition, at parturition, and on days 1, 14, 21 and 30 after parturition) than normal group. Cows with lameness presented higher (P < 0.05) values of body condition score on days -18, -12 and -8 before parturition, and lower (P < 0.05) values on days 7, 14, 21, 30, 45 and 60 after parturition than normal cows. Milk production was lower (P < 0.05) for cows with lameness (on days 7, 14, 21, 30, 45 and 60 after parturition) than normal cows. Discussion: The overall prevalence of lameness in the evaluated period was 22.92% (11/48). Among lame cows, 07 presented laminitis, 02 had interdigital hyperplasia and 02 had sole ulcer. Our findings prove that the biochemical profile and productivity of dairy cows during the peripartum and postpartum period were affected by lameness at the early lactation.